PENGARUH DEBT EQUITY RATIO (DER), RETURN TO ASSETS (ROA), DAN CURRENT RATIO (CR) TERHADAP HARGA SAHAM INDUSTRI MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2018-2020 - Jeshika (Universitas Sains dan Teknologi Komputer, 2023)
This study aims to examine and analyze the effect of the Debt Equity Ratio, Return On Assets and Current Ratio on stock prices. The population used in this study are all manufacturing companies listed on the Indonesia Stock Exchange in three periods, namely 2018-2020. The sampling method used in this study was purposive sampling so that the data was obtained after outlayering 210 samples. The analytical method in this study is multiple linear regression analysis using SPSS 18 software. The results of this study prove that Return On Assets (ROA) has a positive and significant effect on stock prices, but the Debt Equity Ratio (DER) and Current Ratio (CR) do not effect on stock prices.